Finding our way : Jewish texts and the lives we lead today - Holtz, Barry W. (Jewish Publication Society, 2005)
The ancient rabbis believed that the world rests on three pillars: study, worship, and good deeds. It is said that the greatest of these is study, for it leads to the other two. But exactly how does the modern Jewish reader go about studying the Mishnah, Talmud, and Midrash-the great ancient and often hard-to-comprehend texts of our tradition? And how do we glean the great insights and wisdom from these sacred texts, which inspired our ancestors, and apply them to our modern lives? With guidance from renowned author and educator Barry Holtz, these ancient texts take on new meaning for us. He p.